The Determinate Factors to Wildlife Consumption of People in Urban Areas in Lao PDR - Kyophilavong, Phouphet (International Journal of Multidisciplinary in Management and Tourism, 2020)
The study of the determinate factors to wildlife consumption of people in urban areas in Vientiane capital, Bolikhamsay, Khammouane, Savannakhet and Champasak. The results of the study found that most people consume wildlife. The wildlife consumption will include consumption by consumers who do not buy themselves and consumers as buyers themselves. But consumer consumption by the buyer itself is more than that, indicating that Lao people’s wildlife consumption is not consumed, for survival but for consumption in the form of Felicity. In addition, consumption is mainly during the period of wildlife (during the rainy season) where the consumption of wildlife of the population does not take into account the effects. But it is thought to be delicious meat and is consumed without respect for the laws. But not only the people who do not respect the laws of the state—the state also has state officials who are the core of the Lao people, which has not yet complied with the laws set out in the self-styled, rule-makers, and forced to use in the area. However, there is still a significant proportion of the population involved in the protection of wildlife, respect for wildlife regulations that the government has set up without hunting and wildlife trade, which is a threat to the population of wildlife. The factors that determine the consumption of wildlife of the population are as follow gender, education, occupation, belief, and law affects the consumption of wildlife of the population, but the factors of faith and legal factors are more influential than other factors. Among these factors are only legal factors that are negative or contradictory to wildlife consumption, while other factors contribute to the consumption of wildlife of the population.